2020
DOI: 10.1097/htr.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

A Within-Subjects Comparison of Clinical Outcomes for Patients' First and Second Concussions

Abstract: Objectives: To examine the difference between an individual's first and second concussion using a comprehensive, multidomain assessment including symptoms, neurocognitive, vestibular, ocular, and individual demographic and medical history risk factors associated with protracted recovery. Setting: Concussion Specialty Clinic. Participants: Seventy-three patients (aged 13-21 years; 57% female) diagnosed with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…15 Our findings coincide with previous research suggesting that those with a history of migraine or other headaches are at an increased risk of sustaining a repeat concussion 2 and an initial concussion. 19 This differs from the findings of French et al 20 who reported that a history of migraines was not associated with sustaining a repeat concussion and did not prolong recovery. This may be because of the within-subjects study design of the current study, which did not include a comparison group.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…15 Our findings coincide with previous research suggesting that those with a history of migraine or other headaches are at an increased risk of sustaining a repeat concussion 2 and an initial concussion. 19 This differs from the findings of French et al 20 who reported that a history of migraines was not associated with sustaining a repeat concussion and did not prolong recovery. This may be because of the within-subjects study design of the current study, which did not include a comparison group.…”
Section: Discussioncontrasting
confidence: 60%
“…Within our cohort, initial symptom severity scores were higher for their repeat versus initial concussion, which differs from previous studies showing no difference. 20,27 We also found amnesia to be more common after initial concussion, which has not been previously described to our knowledge. 27 Presentation or severity of an initial concussion may have an impact on the prevalence of future concussions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation